Християнсько-поганське світобачення українців на прикладі похоронних пісень з Поділля (село Гусятин Хмельницької області) - Стрілець, Інна Валеріївна (Лінгвостилістичні студії, 2021)
The dirges that were written down in Podilia region in the 21st century and, as we firmly believe with reference to the credible sources documented by metropolitan Hilarion and Hilarion Sventsitskyi, are known as the works of medieval monks who were also poets, present both Christian and pagan conceptions of the world. These songs are best represented in symbols and rites. Among pagan symbols there are as follows: 1. Trees that were previously planted on graves (guelder rose, birch) and that later became a prototype for cross and resurrection. 2. Birds that were going to come to these trees (e.g. cuckoo, cranes migrating south, i.e. a place where the souls of the dead went to according to pre-Christian beliefs, and other birds (non-specified). 3. Comprehensive description of grave as a house of rest on a day of funeral and at the times of active remembrance, i.e. a week after God’s Resurrection on Thomas Sunday (or as a trace back to a pagan rite of remembrance during Midfeast of Pentecost. 4. Conceptual symbol of way (road), which is actively mentioned in lyrics when dead body is carried / taken to graveyard, is yet another piece of evidence for a pre-Christian tradition that lives on keeping detailed instructions to the rite procedure. 5. In particular, this is where another pagan conceptual symbol bread (food) is actively implemented as it accompanied the dead on their way. The topic of ritual food was continued in the next part of the funeral, i.e. meal, which, in its own turn, echoes pre-Christian funeral feast. Soul had to be satisfied so that it would not take a revenge on relatives. Therefore, remembrance meal is organised on the day of the funeral, as well as on the 9th and 40th days after burying and on the anniversary. Moreover, the evidence of paganism and Christianity combination is apocrypha that are sung at the funeral. The plot of these is to describe the Way of the Cross and empathy of Christ’s disciples, as well as to depict comprehensively (including fragments with dialogues) the model of behaviour of the Mother of God. Regarding motifs, Ukrainian authors of the poetical works at the funeral used what was considered to be topical in ancient eastern and western rites. These were similar in nature, including appealing to God and the Mother of God, grief for the dead and warning for the living.
Christian and pagan conception of the world of Ukrainians illustrated in the dirges from Podilia (the village of Husiatyn, Khmelnytsky region)
Keywords: пісні на погреб, християнство, поганство, зверненість (апеляція), мотив, Поділля. dirges, Christianity, paganism, appealing, motif, Podilia.